Non-invasive in vitro and in vivo monitoring of degradation of fluorescently labeled hyaluronan hydrogels for tissue engineering applications. (15th January 2016) - Zhang, Yu; Rossi, Filippo; Papa, Simonetta; Violatto, Martina Bruna; Bigini, Paolo; Sorbona, Marco; Redaelli, Francesca; Veglianese, Pietro; Hilborn, Jöns; Ossipov, Dmitri A.
Graphical abstract: Abstract: Tracking of degradation of hydrogels-based biomaterials in vivo is very important for rational design of tissue engineering scaffolds that act as delivery carriers for bioactive factors. During the process of tissue development, an ideal scaffold should remodel at a rate matching with scaffold degradation. To reduce amount of animals sacrificed, non-invasive in vivo imaging of biomaterials is required which relies on using of biocompatible and in situ gel forming compounds carrying suitable imaging agents. In this study we developed a method of in situ fabrication of fluorescently labeled and injectable hyaluronan (HA) hydrogel based on one pot sequential use of Michael addition and thiol-disulfide exchange reactions for the macromolecules labeling and cross-linking respectively. Hydrogels with different content of HA were prepared and their enzymatic degradation was followed in vitro and in vivo using fluorescence multispectral imaging. First, we confirmed that the absorbance of the matrix-linked near-IR fluorescent IRDye® 800CW agent released due to the matrix enzymatic degradation in vitro matched the amount of the degraded hydrogel measured by classical gravimetric method. Secondly, the rate of degradation was inversely proportional to the hydrogel concentration and this structure–degradation relationship was similar for both in vitro and in vivo studies. It implies that the degradation of this disulfide cross-linked hyaluronan hydrogel in vivo can be predicted basing on the results of its in vitro degradation studies. The compliance of in vitro and in vivo methods is also promising for the future development of predictive in vitro tissue engineering models. Statement of significance: The need for engineered hydrogel scaffolds that deliver bioactive factors to endogenous progenitor cells in vivo via gradual matrix resorption and thus facilitate tissue regeneration is increasing with the aging population. Importantly, scaffold should degrade at a modest rate that will not be too fast to support tissue growth nor too slow to provide space for tissue development. The present work is devoted to longitudinal tracking of a hydrogel material in vivo from the time of its implantation to the time of complete resorption without sacrificing animals. The method demonstrates correlation of resorption rates in vivo and in vitro for hydrogels with varied structural parameters. It opens the possibility to develop predictive in vitro models for tissue engineered scaffolds and reduce animal studies.